Measuring Youth Well-being How a Pan-European Longitudinal Survey Can Improve Policy (Children's Well-Being: Indicators and Research,, 2018)
This volume presents key findings from the EU funded Measuring Youth Well-being (MYWeB) project which assessed the feasibility of a European Longitudinal Study for Children and Young People (ELSCYP). It draws on the original empirical data from a panel of experts in the field of child well-being as well as field experiences from a number of European countries. MYWeB explored strategies and methodological challenges for involving children and young people in well-being research in order to fight poverty and social exclusion. It does so by evaluating different options to measure the well-being of children and young people across Europe using a child centric approach. Written by experts researching children and young people from a variety of disciplinary backgrounds in the areas of sociology, psychology, political science, education, philosophy, economics, social policy, and evaluation.